Reproductive Biology of the Epiphytic Bromeliad Werauhia gladioliflora in a Premontane Tropical Forest - Cascante Marín, Alfredo (2005)
The floral phenology, fruit and seed production, and self-compatibility of Werauhia gladioliflora, an epiphytic bromeliad with a wide distribution, were studied in a premontane forest in the Monteverde area in Costa Rica. The species presents the pollination syndrome of chiropterophily, and it is visited by the small bats Hylonycteris underwoodi and Glossophaga commissarisi (Glossophaginae). The population flowering period extended from October to early December (end of rainy season) and seed dispersal occurred from February to April (dry season). Most plants opened a single flower per night, either every day or at one-day intervals during the flowering period. In natural conditions, the average fruit set amounted to almost half of the potential output, but individual fecundity (number of seeds) remained high. Seed number per fruit and germination capacity after artificial selfing and out-crossing treatments did not differ from natural pollination conditions. Werauhia gladioliflora exhibited high levels of autonomous self-pollination and self-compatibility at the individual and population level, characters associated with the epiphytic habitat. These reproductive traits are also associated with early colonizer species, yet life history traits, such as seed dispersal, seedling establishment success, and growth, are likely to have a major role in determining the presence of this species in the successional vegetation patches scattered over the studied premontane area.